Effects of the Addition of Glucose, Sodium Bicarbonate, and Vitamin E to the Drinking Water of Pre-Slaughter Broiler Chickens on Carcass Yield, Gastric Emptying and Meat Quality - Petrolli,TG (2016)
ABSTRACT An experiment was conducted of the poultry facilities of La Salle Agricultural College in Xanxerê, SC, Brazil, to evaluate the effect of the administration of sodium bicarbonate, glucose and vitamin E to the drinking water during pre-slaughter feed withdrawal on carcass yield, organ relative weights (heart, liver, proventriculus, and gizzard), gizzard emptying, and meat quality of broiler chickens. The applied treatments were: water as control; 50g/L of glucose; 50g/L de glucose + 200mg/L of vitamin E; 75g/L of glucose; 75g/L + 200mg/L of vitamin E; 0.45% of sodium bicarbonate; 0.45% of sodium bicarbonate + 200mg/L of vitamin E; 0.55% of sodium bicarbonate; 0.55% of sodium bicarbonate + 200mg/L of vitamin E; 200mg/L de vitamin E. On the last day before slaughter, during the water diet period,500 birds were distributed in a completely randomized experimental design with ten treatments and ten replicates of five birds each. No difference in broiler carcass yield and organ relative weights was found. There were no significant changes in gizzard contents, in ultimate meat, cooking loss, shear force value, or in the meat color parameters L* (lightness), a* (redness) and b* (yellowness). It was concluded is that the addition of glucose, sodium bicarbonate, and vitamin E to the drinking water during pre-slaughter feed withdrawal period has no influence on carcass yield or on relative organ weight, neither on the emptying of the gizzard contents and the meat quality of broiler chickens.